2021
DOI: 10.1121/10.0007837
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic scene modeling for echolocation in bottlenose dolphin

Abstract: The biosonar of bottlenose dolphins has been shown to have excellent target discrimination performance in cluttered environments, but how the animals process the flow of information used in their adaptive searching process is still an open question. In this work, we present a physics-based model of the process echolocating dolphins may use during target discrimination tasks and validate the model with experimental results. Assuming that dolphins emit biosonar clicks and continuously compare the return echoes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, near-field measurements are not always available, e.g., in-vivo tissue diagnostics. Nevertheless, it has also been shown that echolocating animals use far-field scattered wave to discriminate acoustically small objects such as fish [17], which suggests that the information contained in the diffracted fields could be extracted from far-field single point measurements.…”
Section: Introductionmentioning
confidence: 99%
“…However, near-field measurements are not always available, e.g., in-vivo tissue diagnostics. Nevertheless, it has also been shown that echolocating animals use far-field scattered wave to discriminate acoustically small objects such as fish [17], which suggests that the information contained in the diffracted fields could be extracted from far-field single point measurements.…”
Section: Introductionmentioning
confidence: 99%